Paradoxical Effect of LTB4 on the Regulation of Stress-Induced Corticosterone Production - Locachevic, Gisele A.; Prado, Morgana K. B.; Zoccal, Karina F.; Pereira, Priscilla A. T.; Sorgi, Carlos A.; Bortolanza, Mariza; Peti, Ana Paula F.; Fogaça, Manoela V.; Guimarães, Francisco S.; Del Bel, Elaine; Faccioli, Lúcia H. (Frontiers in Behavioral Neuroscience, 2019)
Depression is a mental illness with a complex and multifactorial etiology, which has been associated with stress and inflammation. Infections, autoimmune diseases, envenomation, and trauma induce an inflammatory response that is characterized by increasing levels of circulating cytokines (e.g. IL-1β) and lipid mediators (e.g. PGE2 and LTB4). Recently, we showed that LTB4 production by the 5-lipoxygenase (5-LO) pathway regulates IL-1β and PGE2 release, reducing tissue damage in a model of sterile inflammation. Since IL-1β and PGE2 increase in serum of stressed patients and potentially trigger depression, we used an animal model of chronic unpredictable stress (CUS) to investigate the potential impact of LTB4 over depression-like symptoms. At basal conditions, 5-LO deficiency (Alox5-/-) reduces the preference for sucrose, while inducing a higher immobilization time on the tail suspension test when compared 129sv. Moreover, Alox5-/- mice present increased caspase-1 expression and elevated levels of IL-1β, IL-17 and PGE2 in the spleen, with increasing corticosterone levels in the frontal cortex but reducing systemic levels. Compared to 129sv mice, CUS induced higher levels of systemic, frontal cortex and hippocampal corticosterone, and also reduced sucrose preference, increased levels of splenic IL-1β, IL-17 and PGE2 and reduced levels of LTB4. Interestingly, CUS exposure did not alter the reduced sucrose preference shown by Alox5-/- mice but greatly enhanced splenic PGE2 production. Compared to Alox5-/- mice at basal conditions, CUS exposure also increased levels of systemic corticosterone, which remained lower than those of CUS-129sv animals. We also observed that treatment with LTB4 decreased caspase-1 expression and systemic levels of corticosterone in CUS-Alox5-/- mice but there was no significant impact on the reduced sucrose preference. Our results demonstrate that LTB4 controls the hypothalamic-pituitary-adrenal (HPA) axis by regulating levels of systemic corticosterone associated with the repression of caspase-1 expression and production of inflammatory mediators. One limitation of our study is that 129sv and Alox5-/- mice were not littermates, not sharing, therefore, the same intra-uterine and preweaning environment. Even so, taken together our results indicate that 5-LO activity is critical for the regulation of stress-induced symptoms, suggesting that the Alox5-/- mouse could be a natural model of corticosterone-independent reduced reward sensitivity.